Consumer Perception and Awareness of Street Food in Guwahati City - Sanmathi, Trinh Thi; Hibo, Atosu (Journal of Global Economy, Business and Finance, 2025)
Street foods are the foods that are very much popular in different parts of the world due to their uniqueness, difference in flavors and affordability. People prefer eating street food due to low cost and easy accessibility. The aim of the present study is to determine consumer’s perception towards street food and also to analyse consumer’s awareness about food safety and hygiene in the main streets of Guwahati city. A survey was conducted on 100 consumers in the main streets of Guwahati city. The findings in the study showed that consumers prefer to eat street food due to their unique taste and flavour. The study also found out that majority of the consumers are aware about food safety and hygiene and almost 83% of the consumers have knowledge about food borne disease that occurs from unhygienic food. Governments should try to promote educational campaigns and advertisements about food safety and hygiene in different parts of the country so that consumers can acquire knowledge about food borne diseases.